Case for diagnosis. Patch granuloma annulare - Geraldo Magela Magalhães; Cássio Ferreira Guimarães; Maysa Carla de Paula (Sociedade Brasileira de Dermatologia, 2017)
Abstract A 59-year-old woman reported a 20-day history of slightly scaly erythematous infiltrated patches on her palms and soles with a histopathological result which was consistent with interstitial-pattern granuloma annulare, clinically classified as patch granuloma annulare. This is a rare clinical variant of granuloma annulare, with an unknown incidence and characteristic clinical and histopathological features. The patient evolved with a complete remission of the lesions after biopsy and the use of high-potency topical corticosteroid.